TWO DECADES OF CHANGE IN ISCHEMIC HEART DISEASE BURDEN IN INDONESIA BASED ON RISK FACTORS - Safaryna, Alifia Merza; Artanti, Kurnia Dwi; Indriani, Diah (Universitas Airlangga, 2025)
The burden of ischemic heart disease (IHD), measured in disability-adjusted life years (DALYs), has significantly increased in Indonesia over the past two decades, indicating that current policies and programs have not been fully effective. This study aimed to analyze changes in the burden of IHD and its associated risk factors from 2002 to 2021 across 34 provinces in Indonesia, using secondary data from the Global Burden of Disease 2021. This cross-sectional analytical study used IHD-related DALYs as the dependent variable, and independent variables included non-optimal temperature, low physical activity, tobacco use, risky dietary patterns, air pollution, obesity, hypertension, high LDL cholesterol, and high fasting glucose. Descriptive statistics and linear regression were used, with Principal Component Analysis (PCA) applied to reduce multicollinearity. Separate regressions were conducted for 2002 and 2021 to assess changes over time. The results showed a 10.5% increase in IHD-related DALYs, from 2,753.87 per 100,000 population in 2002 to 3,043.08 in 2021. Hypertension emerged as the leading risk factor, followed by risky dietary patterns. Tobacco use and a principal component (low physical activity, risky dietary patterns, obesity, high LDL cholesterol, hypertension, and high fasting glucose) significantly contributed to the burden of IHD in both years. Environmental factors such as non-optimal temperature and air pollution did not show significant effects. Health programs must be strengthened with a focus on seven key risk factors contributing to IHD-related DALYs, especially modifiable ones like low physical activity, risky dietary patterns, and tobacco use to reduce IHD burden in Indonesia.